REDESAIN KURIKULUM PENDIDIKAN TINGGI ISLAM: STRATEGI DALAM MENYONGSONG ERA REVOLUSI INDUSTRI 4.0 - Helaluddin Helaluddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
Nowadays, the current development had a big impact on the education system. The era of industrial revolution 4.0 is changing the world through digital technology to enforce the field of education to be adjusted to avoid the outdated education system. Similarly, Islamic higher education must upgrade to front the industrial revolution this time by administering the variety of efforts in improving the quality of education. One of them is redesigning the current KKNI curriculum to integrate some skills that must be mastered by graduates in the era of the fourth industrial revolution. Some of the steps taken in redesigning the curriculum are the review of graduates competency and the course rationalization, the implementation of new literacy programs in education, and the application of blended learning